2005
DOI: 10.1016/s0753-3322(05)80003-4
|View full text |Cite
|
Sign up to set email alerts
|

Does Schumann resonance affect our blood pressure?

Abstract: Objectives-To investigate whether Schumann resonance (SR) affects blood pressure (BP), heart rate (HR), and depression and, if so, whether the putative BP reactivity to SR (BPR-SR) is associated with health-related lifestyle (HLS), disease-related illnesses (DRI), and depression.Methods-A sample of 56 adults in Urausu, Hokkaido, Japan, wore an ambulatory BP monitor, except for the time in the shower, for seven consecutive days. They completed the Geriatric Depression Scale-Short Form and a health survey questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 18 publications
2
28
1
Order By: Relevance
“…Previous reports have not found gender differences [7,9], but there is some evidence for such differences in the effects of various types of magnetic field [26][27][28][29][30][31]. Our results do not agree with some studies in which suicide numbers were found to be inversely related to geomagnetic activity [12,13].…”
Section: Discussioncontrasting
confidence: 99%
“…Previous reports have not found gender differences [7,9], but there is some evidence for such differences in the effects of various types of magnetic field [26][27][28][29][30][31]. Our results do not agree with some studies in which suicide numbers were found to be inversely related to geomagnetic activity [12,13].…”
Section: Discussioncontrasting
confidence: 99%
“…In male rats, the relationship was a positive correlation, but in female rats the relationship was a negative correlation. This finding corresponds with evidence for sex differences in the effects of various types of magnetic field [12][13][14][15][16][17].…”
Section: Discussionsupporting
confidence: 87%
“…Using a sample of 56 adults, 30 males and 26 females, ages between 24 and 73 years in Urausu Hokkaido, Japan for seven consecutive days, Mitsutake et al (2005) found that blood pressure was lower for the days of enhanced amplitude of the Schumann resonance (see below) as compared with quiet day; subjective health and depression were not associated. Men had a higher blood pressure than women during periods of increased resonance amplitude.…”
Section: Several Illnessesmentioning
confidence: 99%